Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Video Terhadap Kemampuan Bepikir Kritis Siswa SMAN 13 Samarinda Pada Materi Bakteri: Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Video Terhadap Kemampuan Bepikir Kritis Siswa SMAN 13 Samarinda Pada Materi Bakteri - Rifky; Purwati, Sri; Herliani; Lumowa, Sonja V.T (PendIPA Journal of Science Education, 2025)
This research aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by video media on the critical thinking abilities on the material Bacteria. The ability to think critically is an important competency for the 21st century that needs to be developed in the biology learning process, especially in abstract and complex material such as bacteria. The research method used was quasi-experimental with a pretest-posttest control group design. The research sample consisted of two classes selected purposively, namely the experimental class which received the PBL model treatment assisted by video media, and the control class which used the conventional learning model. The instrument used is a critical thinking test which was developed based on critical thinking indicators according to Ennis. The data analysis technique used is the Independent Sample t-Test with a significance level of 5%. Based on the results of data analysis, it was found that the t test on students' critical thinking skills showed a significance value (0.000 < 0.005). Thus, it can be concluded that there is a significant influence from the use of the Problem Based Learning learning model assisted by video media on students' critical thinking skills in the Bacteria material.